LABPSA: Youth Expression and Tolerance Practices Digitalization to Prevent Religious Disputes in Aceh - Husna, Fathayatul (Sunan Kalijaga: International Journal of Islamic Civilization, 2023)
This article begins with an academic discourse on tolerance campaign strategies as a new form of conflict resolution. This strategy focuses on how young people optimize social media to campaign for tolerance issues. The research used virtual ethnographic methods and online documentation to collect data. This step examined the landscape of religious conflicts in Indonesia, especially in Aceh province. What is the role of the Aceh government in resolving religious conflicts in Aceh? What is the form of young people’s active participation when voicing the issue of tolerance through LABPSA? The research results are that the presence of young people under the LABPSA institution is a new way to voice acts of tolerance and resolve religious conflicts in Aceh. They also criticize the Aceh government in response to the issue of intolerance. The presence of young people in LABPSA is also part of helping the Aceh government resolve conflicts in Aceh, especially religious conflicts, and eradicate intolerance issues.